(untitled) (Texas Journal of Engineering and Technology, 2023)
Silencers and cleaning methods in the exhaust system of automobile engines are analyzed. The processes of liquid, thermal and catalytic decontamination of exhaust gases have been tested. The efficiency of the design of the catalytic converter has been determined and it has been established that the closer it is located to the combustion chamber, the more efficient it will work.